PENGARUH INTENSITAS SCREEN TIME TERHADAP MOTIVASI DAN KONSENTRASI BELAJAR IPA SISWA KELAS V SEKOLAH DASAR - Fajri, Muzdalifah; Adira, Adelia; Putri, Nabila; Faisal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of screen time intensity on learning motivation and concentration in fifth-grade elementary school science students. The increasing use of digital devices by students raises concerns about its impact on the learning process, particularly motivation and concentration. This study used a quantitative approach with a survey method by distributing questionnaires to 20 respondents. Data analysis was conducted using validity, reliability, normality, Spearman correlation, and simple linear regression tests. The results showed that screen time intensity did not have a significant effect on students' learning motivation or concentration (p > 0.05). However, there was a significant positive relationship between learning motivation and concentration with a correlation coefficient of 0.603 and a significance of 0.005 (p < 0.05). This finding indicates that the higher a student's learning motivation, the better their concentration level. Thus, the effect of screen time on the learning process is not direct, but is influenced by the type of use, duration, and environmental supervision. Therefore, improving the quality of learning needs to be focused on strengthening learning motivation and managing gadget use wisely.